PENGEMBANGAN ENSIKLOPEDI IPATERPADU BERBASIS POTENSI LOKAL SEBAGAI BAHAN AJAR MANDIRI BAGI SISWA SD/MI - Dian Noviar; Sulistiyawati Sulistiyawati (Universitas Sebelas Maret, 2014)
The study entitled Development of Self Instructional Natural Science locally Based Encyclopedia for SD/MI Students was done considering the development of innovative teaching materials still draw little attention. The development could increase teacher quality in teacing science. This research belong to research & development category with ADDIE model (Analysis, Design, Development & Production, Implementation, Evaluation) . The study was conducted in January-April 2013 in the Madrasah Ibtidaiyah Negeri Tempel, Sleman. A set of questionnaire sheet were used to get an assessment of students understanding of learning , independent learning, active learning, interests, and the use of encyclopedias. Data covering eight aspects of the 29 assessment criteria. Data analysis was carried out to see the value of each aspect or descriptor in the questionnaire. The collected data were analyzed by calculating the mean score obtained. Development of Self Instructional Natural Science locally-Based Encyclopedia produce Encyclopedia of bird species in some areas of Yogyakarta namely: Gembiraloka zoo, cagar alam Gunung Gamping, suaka marga satwa Paliyan, dan cagar alam Imogiri. Assessment from reviewers, peer reviewers, and teachers reveal that the quality of the encyclopedia is very good. Student assessment indicates that the quality of the encyclopedia also very good. Such also whole aspect percentage 93,79 % are very good category. Student evaluation showed Integrated IPAs encyclopaedia quality in very good category. And also Integrated IPAs encyclopaedia based on student response have 89,72%.Keywords: Encyclopedia, Natural Sciences, locally-based, elementary school/MI.